2020
DOI: 10.3390/su12083297
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for the Life Cycle Cost of Power Grid Projects by Employing a System Dynamics Technique: A Power Reform Perspective

Abstract: In the context of China’s electric power reform, issued in May 2019, the “Transmission and Distribution Pricing Supervision Measures” have changed asset accounting in grid enterprises and therefore affected cost accounting in grid projects. This paper proposes a dynamic cost calculation model based on system dynamics and takes a power grid company as an example. On this basis, a sensitivity analysis of power grid engineering was conducted to determine the impacts of key factors of power reform on life cycle co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Thirdly, the fuzzy reference comparisons for "Promoting employment benefit", C6, were conducted, and Table 3 lists the result. Then, the A W is: Finally, the optimal fuzzy weights of the eight benefit sub-criteria from the comprehensive benefit evaluation of a power grid investment can be calculated according to Equations ( 8)- (11), which are shown in Figure 4. Moreover, the CR is 0.0455, which is less than 0.1.…”
Section: Calculating the Weights Of The Benefit Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, the fuzzy reference comparisons for "Promoting employment benefit", C6, were conducted, and Table 3 lists the result. Then, the A W is: Finally, the optimal fuzzy weights of the eight benefit sub-criteria from the comprehensive benefit evaluation of a power grid investment can be calculated according to Equations ( 8)- (11), which are shown in Figure 4. Moreover, the CR is 0.0455, which is less than 0.1.…”
Section: Calculating the Weights Of The Benefit Criteriamentioning
confidence: 99%
“…Under the new transmission and distribution policy, power grid enterprises charge grid fees based on fixed transmission and distribution electricity prices instead of earning the difference between the transmission and sales prices [11]. This functional orientation and operation mode change makes the power grid transmission and distribution investment management particularly important.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, [25] researched on life cycle cost analysis which was integrated with dynamic systems in power grid projects. Regarding the research's impact on the calculation of operation and maintenance costs, it will be approached from four perspectives: material costs, repair costs, employee compensation, and other costs, with the goal of making comparisons before and after changes, such as the impact of accounting for operating and maintenance costs after electricity reform, stock changes, and the resulting increase.…”
Section: System Dynamicsmentioning
confidence: 99%
“…Xiang Chen (2022) [7], using the traditional LCC-EL model, introduced the factor of equipment operation reliability and found a reasonable selection scheme for main transformers. Yongli Wang et al, (2020) [8] used sensitivity analysis to explore important factors identified by power policy reforms for the whole life cycle of equipment, redetermined the impact of equipment breakdown on LCC cost analysis, and suggested rules for managing the apportionment of costs incurred by equipment.…”
Section: Introductionmentioning
confidence: 99%
“…While there are some studies [4][5][6][7][8] that have investigated the application of LCC and EL in the energy sector, the depth of the research is still insufficient in the dimensions of data processing, LCC breakdown determination, calculation of LCC, and determination of economic life, as the analytical methods remain imprecise and unscientific. Due to the severe uncertainty of decision environments, decision-makers can benefit from models that incorporate fuzzy analysis.…”
Section: Introductionmentioning
confidence: 99%